Individual pension products offered by banks in Poland: A multidimensional comparative analysis - Joanna Rutecka-Góra (Financial Internet Quarterly, 2021)
The supplementary old-age pension system in Poland consists of group and individual plans. This research covers the latter, namely the individual retirement accounts and individual retirement saving accounts that were introduced in 2004 and 2012 respectively. The main aim of the paper is to conduct a multidimensional comparative analysis of bank retirement products including the linguistic complexity of documents creating the retirement contracts offered to individuals by banks, and the costliness and profitability of such products in the period 2012-2019. Moreover, it identifies the dependencies between the linguistic and economic traits of retirement contracts offered by banks. The correlation analysis conducted using the Spearman's rank correlation coefficient showed that the more readable a document of a bank contract is, the higher the interest rate is and the higher the cancellation fees. The results of the study are relevant for both financial institutions and public bodies as they show the key characteristics that may influence the demand for individual retirement products in Poland and may serve as either a stimulator or a barrier in the development of supplementary old-age pension provision.
Keywords: G21; G23; G51; J26; 330; supplementary pension system; retirement accounts; costliness; readability; efficiency of retirement products; banks